Relationship Between Rheumatoid Arthritis Disease Activity Assessed with the US7 Score and Quality of Life Measured with Questionnaires (HAQ, EQ-5D, WPAI) - Skacelova, Martina; Pavel, Horak; Zuzana, Hermanova; Katerina, Langova (Current Rheumatology Reviews, 2017)
Background: Rheumatoid arthritis is a chronic disease considerably affecting the quality of life of patients, their functional abilities and capability to work. In everyday clinical practice, the condition is commonly monitored by assessing the disease activity using a joint count and laboratory markers of inflammation with calculating the DAS28 or other systems for scoring the disease activity. Objectives: This study is aimed to evaluate the benefit of ultrasound examination with a standardized instrument and correlate its results with the quality of life of patients and their functional abilities as assessed by standardized questionnaire methods. Methods: 98 rheumatoid arthritis patients were assessed clinically for disease activity and ultrasound examination with assessment of German US 7 score was performed. The data from patientreported outcomes (Stanford Health Assessment Questionnaire and the EQ-5D instrument) were collected. Results: The results of ultrasound examination were correlated with both disease activity and patient- assessed quality of life and limitations to daily activities. A very good predictor of impaired quality of life mainly appears to be the presence of synovitis detected by grayscale (GS) ultrasonography, shown to be significantly negatively correlated with patient mobility (r=-0.268, p=0.017), self-care (r-0.349, p= 0.002) and usual activities (r=-0.264, p= 0.019) as well as with patients’ global health assessment (r=-0.243, p= 0.031). Conclusions: The study results showed a direct relationship between rheumatoid arthritis activity assessed with the US7 and patients’ impaired functional abilities, mobility, self-care and usual activities.
Keywords: therapeutic